“Freedom from themselves” gendered mechanisms of control, power, and resistance in prison dog training programs - Button, Andrea (Kansas State University, 2007)
During the past twenty-five years, the number of prison programs in which inmates train dogs has increased rapidly. A lack of systematic studies to address the effects of these programs on staff and inmates has led to limited, anecdotal accounts of the impact of these programs on correctional institutions and their occupants. In addition, an analysis of differences in these effects for men and women is missing. This paper proposes to bridge this gap through qualitative research conducted in two Kansas prisons (a men’s and a women’s institution) in which inmates train assistance dogs and dogs made available for adoption by the general public. Drawing primarily on the works of Erving Goffman, Michel Foucault, and Jill McCorkel, I focus on the mechanisms of social control and resistance within these programs and their effect on the inmates participating in the program, utilizing a gendered analysis throughout. Using the experiences of the men and women in these programs, as well as those of correctional staff and community members, I propose that these programs provide an important outlet for resistance for the participants.
Keywords: Social control; Resistance; Prison; Gender; Sociology, General (0626)